2008
DOI: 10.1177/0146167207311200
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Contact: Intergroup Contact in the Context of Power Relations

Abstract: This work investigated how group-based power affects the motivations and preferences that members of advantaged and disadvantaged groups bring to situations of contact. To measure the preferred content of interactions, desires to address particular topics in intergroup contact were assessed for both experimental groups (Study 1) and real groups (Study 2). As predicted, across both studies, the desire to talk about power was greater among members of disadvantaged than of advantaged groups. This difference was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
258
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(295 citation statements)
references
References 23 publications
(32 reference statements)
23
258
1
2
Order By: Relevance
“…That is, low-power group members' greater preference, relative to that of high-power group members, to discuss points of difference occurred because they had a greater motivation for a change in the power structure. Saguy et al (2008) also obtained this pattern of preference to discuss commonality and difference with members of real groups differing in social status and power in Israel and so replicated the mediating effect of motivation for social change on interest in talking about group differences. In addition, members of the highstatus group (Ashkenazim) who were more highly identified with their group displayed greater interest in talking about commonality, whereas members of the low-status group (Mizrahim) who were more highly identified with their group showed a greater preference to talk about differences.…”
Section: Establishing and Reestablishing Preferred Representationsmentioning
confidence: 61%
See 2 more Smart Citations
“…That is, low-power group members' greater preference, relative to that of high-power group members, to discuss points of difference occurred because they had a greater motivation for a change in the power structure. Saguy et al (2008) also obtained this pattern of preference to discuss commonality and difference with members of real groups differing in social status and power in Israel and so replicated the mediating effect of motivation for social change on interest in talking about group differences. In addition, members of the highstatus group (Ashkenazim) who were more highly identified with their group displayed greater interest in talking about commonality, whereas members of the low-status group (Mizrahim) who were more highly identified with their group showed a greater preference to talk about differences.…”
Section: Establishing and Reestablishing Preferred Representationsmentioning
confidence: 61%
“…In a pair of studies, one with laboratory groups and the other with ethnic groups varying in status in Israel (Ashkenazim, high status; Mizrahim, low status), Saguy et al (2008) provided evidence in support of this hypothesis. In the laboratory study, group position was manipulated by giving one group control over valued resources (experimental credit) for both groups.…”
Section: Establishing and Reestablishing Preferred Representationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, members of advantaged subgroups may unconsciously or strategically choose to promote inauthentic messages that obscure and draw attention away from group-based role and status differences and power (Jackman, 1994;Ruscher, 2001). Saguy, Dovidio, and Pratto (2008) found that, when given a choice of topics to discuss, members of lower status subgroups preferred to talk about topics related to group differences, whereas members of higher status subgroups displayed greater desire to talk about topics addressing commonalities between the subgroups. In actual interaction between high -and low -status subgroup members, discussions typically gravitate in an clearly inauthentic, selfalienated way to commonality.…”
Section: Subgroup Differentiation and Hierarchymentioning
confidence: 97%
“…In contrast, disadvantaged subgroup members display greater support for ideologies and mentality that de-legitimize existing system structure (e.g., endorsement of human rights, humanitarianism in an exploitative or tyrannical social system) and have a greater self-congruent desire for egalitarian changes in the relationship between the subgroups (Saguy, Dovidio, & Pratto, 2008). The status of subgroups within a larger group, organization, community or society not only defines the roles and relations of their members, but also shapes members' authenticity in experiencing and expressing their psychological needs, feelings, values, attitudes and personal identity.…”
Section: Subgroup Differentiation and Hierarchymentioning
confidence: 99%